Involvement of Heme Oxygenase-1 Participates in Anti-Inflammatory and Analgesic Effects of Aqueous Extract of Hibiscus taiwanensis. (21st June 2012) - Liu, Shu-Ling; Deng, Jeng-Shyan; Chiu, Chuan-Sung; Hou, Wen-Chi; Huang, Shyh-Shyun; Lin, Wang-Ching; Liao, Jung-Chun; Huang, Guan-Jhong
Abstract : Anti-inflammatory effects of the aqueous extract of Hibiscus taiwanensis (AHT) were used in lipopolysaccharide (LPS-)stimulated mouse macrophage RAW264.7 cells and carrageenan (Carr-)induced mouse paw edema model. When RAW264.7 macrophages were treated with AHT together with LPS, a concentration-dependent inhibition of nitric oxide (NO), tumor necrosis factor (TNF- α ), and prostaglandin E2 (PGE2 ) levels productions were detected. Western blotting revealed that AHT blocked protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and elevated heme oxygenase-1 (HO-1), significantly. In the animal test, AHT decreased the paw edema at the 4th and the 5th h after Carr administration, and it increased the activities of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) in the paw tissue. We also demonstrated AHT decreased the NO, TNF- α, and PGE2 levels on the serum level at the 5th h after the Carr injection. Western blotting revealed that AHT decreased Carr-induced iNOS, and COX-2, and increased HO-1 expressions at the 5th h in the edema paw. These findings demonstrated that AHT has excellent anti-inflammatory activities in vitro and in vivo and thus it has great potential to be used as a source for natural health products.